The Influence of HR Management Strategy and Competitive Advantage on The Performance of UMKM, Sukmajaya District, Depok City, West Java - Oktaviani, Cyka; Udriyah; Sudari, Suci Ayu (International Publisher, 2024)
Micro Small and Medium Enterprises (MSMEs) have experienced positive developments over time, MSME players also produce a variety of products. To determine the effect of competitive advantage on the performance of MSMEs in Sukmajaya District. To find out whether HR Management strategies and competitive advantage have affected the performance of MSMEs in Sukmajaya District, according to the Central Bureau of Statistics for MSMEs in Sukmajaya District, there will be a decline in 2022 - 2023. The method used in this research is a quantitative method. The quantitative approach can be explained as a research method based on positivism philosophy. This method is used as a research tool on a certain population or sample. This research shows that HR management strategies have a positive and significant influence on the performance of MSMEs in Sukmajaya District. MSME performance also has a positive impact on HR Management strategies. Together, HR Management strategy and competitive advantage have a significant effect on MSME performance. Implications for business actors: this research provides direction for effective management regarding HRM strategy and competitive advantage. HR Management Strategy and competitive advantage have a positive and significant effect on the performance of MSMEs in Sukmajaya District, with a significance value of 0.000 and 0.000 0.05. The linear regression results show that the Adjusted R² is 0.876, which means that 87,6% of the MSME performance variables are explained by these two variables. The F test shows F count (81,632) F table 3.130, strengthening the positive and significant influence of these two variables on performance.